2022
DOI: 10.3389/fpsyg.2022.808500
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Online and In-Store Purchase Willingness: Associations With the Big Five Personality Traits, Trust, and Need for Touch

Abstract: Nowadays, customers can utilize both online and in-store retail channels. Consequently, it is crucial for retailers to understand the possible drivers of retail channel selection, including customers’ personalities, degrees of trust, and product touch preferences. Unfortunately, current omnichannel research only scarcely addresses the effects of personality, trust, and desire to touch a product before purchasing it on willingness to purchase and how those effects vary between online and in-store shopping. Thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 94 publications
1
3
0
Order By: Relevance
“…This is line with recent research (for a recent review, see Sindermann et al , 2020), which suggests that, e.g. user personality has a significant impact on technology acceptance particularly in the more modern retailing contexts such as online shopping and omnichannel shopping (Hermes et al , 2022; Hermes and Riedl, 2021). Therefore, our study contributes to the further development of TAM and UGT by highlighting short comings of these theories, specifically concerning the interaction of customer experience, purchase intention and customer irritation in the omnichannel domain.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This is line with recent research (for a recent review, see Sindermann et al , 2020), which suggests that, e.g. user personality has a significant impact on technology acceptance particularly in the more modern retailing contexts such as online shopping and omnichannel shopping (Hermes et al , 2022; Hermes and Riedl, 2021). Therefore, our study contributes to the further development of TAM and UGT by highlighting short comings of these theories, specifically concerning the interaction of customer experience, purchase intention and customer irritation in the omnichannel domain.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, future research might advance these theories to make them applicable in the emerging field of AR. In this regard, future research should especially consider personality as a direct determinant, or as moderator variable, in studies on ARSAA in brick-and-mortar stores as it has shown to have a significant influence technology acceptance (Hermes et al , 2022; Hermes and Riedl, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The Big Five Model of personality is, probably, the most widely used framework for explaining individual differences in populations and relies on five sharply independent traits (4). The model has also been used extensively in the study of human characteristics that have an impact on purchase behaviors [e.g., (5)(6)(7)(8)(9)(10)(11)(12)].…”
Section: Introductionmentioning
confidence: 99%
“…Extraversion also positively influenced intentions to travel (Talwar et al, 2022) and dine‐out (Okubo, 2022) during the pandemic, indicating their reluctance for being confined at home. Extraversion also kindles intentions for breaking Covid‐related rules (Navajas et al, 2021) and willingness to buy in‐store (Hermes et al, 2022). It could be implied that people with higher openness may shop in‐store due to the anticipated experiences of newness offered by the various unexpected stimuli in the store amid the pandemic (e.g., newer signages for social distancing), and people with higher extraversion may show positive intentions for in‐store shopping due to the perceived feeling of not being confined to homes or reflecting one's assertiveness by communicating that it is okay to shop in‐store amid the pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%